Meanings of Objektive und Subjektive Constructions in German Sentences and Their Equivalences in Indonesian - Sulis Triyono (Humaniora, 2017)
This study aims to describe: (1) objektive und subjektive constructions in German sentences, (2) meanings of objektive und subjektive in German sentences, and (3) equivalences of objektive und subjektive in German sentences in Indonesian.This was a qualitative descriptive study. The objects of the research data were lingual units of modality constructions with objective and subjective meanings in both German phrases and sentences. The subjects of the data were modal verbs in German sentences. The data sources were the magazine NADI Indonesia Deutsch Edisi I/No. 16 Tahun 2012, Edisi I/No. 17 Tahun 2013, and Edisi II/No. 18 Tahun 2013. The data were collected by means of reading and noting techniques and analyzed by means of the translational, equivalent, and distributional techniques. The data validity was assessed through the semantic validity and the inter-rater and intra-rater techniques.The research findings are as follows. (1) the objektive construction in German is S - Inf+Modalverb and the subjektive construction is S+Inf – Modalverb. (2) Meanings of objektive are those which are loose in nature because because lexical elements of modality can reveal utterance contents while meanings of subjektive are those outside lexical elements because they are affected by speakers’ subjective intentions. (3) The equivalences of objektive und subjektive in German sentences in Indonesian are in the form können appearing 107 times, equivalent to meanings of dapat, bisa, ada, menjadi, berhasil, mampu, meraih, terdiri, sungguh, and makna zero. Dürfen (8) are equivalent to meanings of dapat, boleh, and makna zero. Modalverb sollen (27) are equivalent to meanings of harus, akan, bisa, seharusnya, perlu, dan makna zero. Wollen (3) are equivalent to meanings of ingin, terus terang, and makna zero. Müssen (31) are equivalent to meanings of harus, dapat, bisa, and makna zero. Möchten (16) are equivalent to meanings of ingin, berminat, perlu, and makna zero.